X would be equivalent to -2 so x=-2
Answer:
12,16
Step-by-step explanation:
16-12= 4 difference
16+12= 28 sum
Answer:
7x+3
Step-by-step explanation:
PEMDAS
multiplication comes first so
3x3=9
9+7x-6
Combine like terms
7x9-6
7x+3
That is your answer since it can't be factored anymore.
Hope this helped
Good luck!
Answer:
Step-by-step explanation:
3×1/2 = 1/2 + 1/2 + 1/2 = 3/2 = 1½
Sinxcosx−1sinxcosx+1=1−cosxsinx1+cosxsinx
sinx−cosxcosxsinx+cosxcosx=sinx−cosxsinxsinx+cosxsinx
sinx−cosxcosx⋅cosxsinx+cosx=sinx−cosxsinx⋅sinxsinx+cosx
sinx−cosxsinx+cosx=sinx−cosxsinx+cosx
hence, proved